2006
DOI: 10.1117/12.668153
|View full text |Cite
|
Sign up to set email alerts
|

Estimate luminance of single panel and dual panel light guide by luminous flux flow

Abstract: This paper presents a mathematical method to estimate luminous flux and luminance of single panel and dual panel light guides based on photometric calculations under various design requirements. The distribution of dot pattern or micro-prism was computed according to those estimated luminous flux on the illuminant surface. The effects of light source efficiency, angular distribution of luminance of light guide, luminous flux ratio and area ratio of main panel with sub panel on luminance of light guide are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The luminous flux provided by each LED is found to be 1.557 lm (=U in /3) and is derived by integrating the relative luminous intensity distribution (given in the LED specification) over the spherical space [5]. The main panel area, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The luminous flux provided by each LED is found to be 1.557 lm (=U in /3) and is derived by integrating the relative luminous intensity distribution (given in the LED specification) over the spherical space [5]. The main panel area, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This problem is evident in many dual-display backlights, in which it is commonly observed that the area of the main panel corresponding to the position of the sub-panel is darker than the remaining panel area [4]. Furthermore, the optical design must not only ensure that both panels are evenly illuminated, but must also maintain the specified luminance difference between the main panel and the sub-panel [5]. Therefore, achieving the specified luminance conditions for the dual-panel display requires a knowledge of the optimum design specifications for the related optical elements, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…This causes the region of the main panel corresponding to the position of the subpanel to be darker than the remaining main panel area since this particular region of the main panel receives relatively less luminous flux than the surrounding area. 10 In addition, a further design difficulty is the necessity to deliver an even luminance of the subpanel irrespective of whether its luminance is to be smaller than, greater than, or equal to that of the main panel. The structural layout of a dual-panel backlight is more complicated than that of a single-panel backlight, and hence it is difficult to know before entering the detailed design phase whether or not the design specifications for the luminance of the main panel and the subpanel can actually be attained.…”
Section: Introductionmentioning
confidence: 99%
“…6 The aim of the light guide design for a dual-panel backlight system is to ensure an appropriate allocation of the received luminous flux between the main panel and the subpanel in order to attain an equal luminance of the two panels. 10 In practice, most light guides are flawed in that their diffuser dot density patterns. 10 tend to direct too much luminous flux flow downward to the subpanel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation